My six-word story: Power to reconnect and connect - Alexie Puran (The Beryl Institute, 2020)
The COVID-19 global pandemic is a threat to the well-being of our healthcare professionals. Recent studies on the mental health effects of healthcare professionals from China and Italy have revealed higher levels of depression, anxiety and psychological distress. As a Pediatric Emergency Medicine physician working on the frontline and a H3 (Helping Healers Heal) Peer Champion, I sought to support my staff's well-being and emotional resilience. My Six-Word Story, a simple and meaningful activity was designed to support the psycho-social well-being of those on the frontline providing care. This new project was implemented in the Pediatric Emergency Department at NYC Health + Hospitals/ Harlem. Six-word stories, a form of micro fiction, have increased in popularity in recent years. The staff participating in the project shared their six-word stories on their inspiration in choosing a career in medicine. After receiving all the submissions, illustrations were added to each story creating a poster story. This project was well received by the staff as it allowed them to be creative, focus on positive thoughts and was not time-consuming. My Six-Word Story is shown to have the power to reconnect with our purpose and connect with each other through common interests, shared beliefs and shared values. This innovative initiative can easily be replicated or adapted to help support the well-being and human experience of all us. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.